Análisis de la cartera vencida y su incidencia en la rentabilidad de la cooperativa de ahorro y crédito pacífico ltda. en la ciudad de Riobamba durante el período septiembre 2014-septiembre 2015. - Bravo Naula, José (2017)
TITLE: ANALYSIS OF THE EXPECTED PORTFOLIO AND ITS INCIDENCE IN THE PROFITABILITY OF THE SAVINGS AND PACIFIC CREDIT COOPERATIVE LTDA. IN THE CITY OF RIOBAMBA DURING THE PERIOD SEPTEMBER 2014-SEPTEMBER 2015. ABSTRACT: The financial analysis makes it possible to show comparative data from one year to the next, because the analysis uses indicators to determine if there is an impact on profitability, this research refers to the study of the analysis of past due portfolio and its incidence on profitability in the “Cooperative Of Savings and Credit Pacific. Ltd”. In order to analysis the past due portfolio, a vertical and horizontal analysis of the financial statements was carried out. Indicators were used to determine the economic reality of the unproductive portfolio, as well as to measure the delinquency ratio in order to consider corrective actions. Chapter I it refers to the problem, approach, formulation, delimitation, justification of the problem and objectives. Chapter II It refers to the collection and bibliographical analysis, which details the theoretical foundations that support the elaboration of the theoretical framework. Chapter III the methodological framework is carried out, which details the type, design of research techniques, as well as the population that is object of study. Chapter IV the results obtained in field research are detailed. Chapter V it contains the conclusions and recommendations, the conclusions reached with the present investigation and their respective recommendations are presented. Chapter VI It is detailed the purpose frame or proposal the same that consists of a title, feasibility, objectives and content. KEY WORDS: analysis of past due loans and their impact on the profitability of COAC.